Negative Politeness Strategies in â€The Menuâ€ Movie - Laila Marfirah; Afriana Afriana (Institut Agama Islam Negeri Palopo, 2023)
The aim of study discovers the different types of negative politeness methods is classified as descriptive qualitative research. The study's findings were derived from words recognized the character